Human Biomonitoring of Butylated Hydroxytoluene (BHT) in Germany: Methods, Exposure Levels, and Health-Based Interpretation - Schmidtkunz, Christoph; Schönrath, Isabell; Murawski, Aline; Küpper, Katja; Lemke, Nora; Weber, Till; Leng, Gabriele; Kolossa-Gehring, Marike (La Medicina del Lavoro, 2025)
Butylated hydroxytoluene (BHT) is an antioxidant which is used in a vast array of consumer products. The most sensitive toxicological endpoints of BHT are hepatic enzyme induction and reproductive effects. Because of its wide dispersive use and its potential relevance for human health, BHT was included in the human biomonitoring (HBM) cooperation between the German Federal Ministry for the Environment and the German Chemical Industry Association. An analytical method for the sensitive determination of 3,5‑di‑tert‑butyl‑4‑hydroxybenzoic acid (BHT acid)—an oxidized metabolite of BHT which is excreted in urine—was developed. This method was then applied in several environmental and occupational HBM surveys, and BHT acid was detected in the vast majority of samples. Health-based guidance values as well as reference values for the interpretation of HBM results were derived for BHT acid. Thus, a fine-grained picture of the current state of BHT exposure in different populations in Germany is now available. Uncertainties arise from large variability in the fraction of dose excreted as BHT acid and incomplete understanding of human metabolism, which limits reverse dosimetry and risk assessment, particularly for children.